The midnight show : a novel - Kelly, Lee; Thorne, Jennifer, 1980- (Crown, 2026)
"She was the breakout star of a new late-night sketch show that would change the tv landscape forever....until she disappeared. This whip-smart, funny novel delves into the cutthroat world of comedy in the 1980s New York to uncover the story of what really happened that night"-- Provided by publisher.